2019
DOI: 10.5812/compreped.83761
|View full text |Cite
|
Sign up to set email alerts
|

Electroencephalogram Abnormalities in Very Young Children with Acute Hepatitis A Infection: A Cross-Sectional Study

Abstract: Background: There is a shortage on studies concerned with electroencephalogram (EEG) abnormalities in neurologically asymptomatic children with acute hepatitis A virus (HAV) infection. Objectives: In the present study, we evaluated EEG patterns in HAV infected children who had no symptoms of overt or minimal hepatic encephalopathy (HE). Methods: Forty-five children infected with HAV infection along with 45 healthy children were studied. EEG was acquired in resting condition with closed eyes. Statistical analys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 25 publications
(37 reference statements)
0
3
0
Order By: Relevance
“…In adult studies, the EEG findings of encephalopathy have been staged as alpha coma, triphasic wave, and periodic patterns; however, these abnormal morphologies were not common in children. On the other hand, the pediatric EEG findings include varying degrees of slowing, unresponsiveness to external stimuli, and discontinued activity [22,23]. In our study, we classified encephalopathic EEG findings into three stages, normal, diffuse slowing, and voltage suppression, which is different from the adult EEG abnormalities.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…In adult studies, the EEG findings of encephalopathy have been staged as alpha coma, triphasic wave, and periodic patterns; however, these abnormal morphologies were not common in children. On the other hand, the pediatric EEG findings include varying degrees of slowing, unresponsiveness to external stimuli, and discontinued activity [22,23]. In our study, we classified encephalopathic EEG findings into three stages, normal, diffuse slowing, and voltage suppression, which is different from the adult EEG abnormalities.…”
Section: Discussionmentioning
confidence: 92%
“…EEG is a valuable diagnostic technique in the identification of encephalopathies. In addition, EEG abnormalities in children occur earlier than in adults [22]. In adult studies, the EEG findings of encephalopathy have been staged as alpha coma, triphasic wave, and periodic patterns; however, these abnormal morphologies were not common in children.…”
Section: Discussionmentioning
confidence: 99%
“…Evidence has shown that EEG can be used as a sensitive and reliable method for screening brain and nerve disorders (10). Many studies have mentioned EEG abnormality as a primary diagnostic sign for brain dysfunction in the absence of overt hepatic encephalopathy (OHE) or minimal hepatic encephalopathy (MHE) (11,12).…”
Section: Introductionmentioning
confidence: 99%